The Downstreaming of Investment Services: A Strategy to Achieve Investment Targets amid the Disruption Era in Lebak District - Barsei, Adhityo Nugraha; Firmansyah, Nurhuda; Kustanto, Munari; Alita, Endriana Wahyu (UI Scholars Hub, 2024)
The COVID-19 pandemic has significantly impacted global community and economy. As the pandemic began to subside, the government initiated various strategies for economic recovery. Investment is one of the policy instruments to improve the local economy. The Investment and One-Stop Integrated Service Agency (DPMPTSP), hereafter coined the Department of Investment, has implemented different strategies to achieve regional investment targets. Data indicate a decline in Foreign Direct Investment (FDI) due to the pandemic, however, an increase in Direct Investment (DI) is also observed, contributing to the achievement of investment targets. This study aims to examine the strategies applied by the Department of Investment of Lebak District to achieve these targets. A qualitative descriptive approach was employed, while data were collected through in-depth interviews and documentation. Data analysis was conducted using ATLAS.ti software by coding data, opening a network, and drawing conclusions from collected data. The results reveal a